The Importance of Mindfulness in Preventing Substance-Abuse Relapse: A Literature Review - Tırışkan, Merve; Onnar, Nilgün; Cömert, Itır Tarı (Addicta: The Turkish Journal on Addictions, 2015)
This study discusses how to use information on mindfulness and its applications as a method for coping with difficult emotions in order to prevent a relapse of drug addiction. Mindfulness practices, while supporting healthy development, also reduce stress, improve well-being, and provide emotional balance. Its use in substance abuse treatment is quite new. Mindfulness helps one to be able to cope with their state of mind in the moment of stress related to substance withdrawal by supporting learning and well-being, and by enabling a direct relationship to be established among self-awareness, self-control, and emotion regulation. In the working group of this study on the prevention of substance abuse relapse, sessions consisted of experimental exercises and discussions. The objective is to keep key points such as the person’s current experiences, relapse, improvement or lifestyle in the center of the discussion. The attention of the participants, through mindfulness application, is a continual in “the moment” review of their surroundings and can prevent them from getting lost in their history. As another strong side of the program, the importance of an individual addressing one’s self before judging or being made to feel guilty is gently encouraged in these applications. In this way, difficulties that emerge in the practice are assessed not as failures but as a sign of tendencies related to the mind, and people’s motivations are protected by normalizing the difficulties they experience. Perhaps the most crucial point of the mindfulness-based relapse prevention program, unlike other therapies, is that labeling in any manner is not performed. Instead of people experiencing the worth of being forgiven, people are required to only observe and accept. Through all of these practices, the target is to ensure a person becomes more aware and accepting towards their actions.
Keywords: Mindfulness; Substance abuse; Difficult emotions; Emotion regulation; Relapse prevention